Review of -omics studies on mosquito-borne viruses of the Flavivirus genus - Peinado, Rafaela dos S. [UNESP] (2022)
Arboviruses are transmitted by arthropods (arthropod-borne virus) which can be mosquitoes or other hematophagous arthropods, in which their life cycle occurs before transmission to other hosts. Arboviruses such as Dengue, Zika, Saint Louis Encephalitis, West Nile, Yellow Fever, Japanese Encephalitis, Rocio and Murray Valley Encephalitis viruses are some of the arboviruses transmitted biologically among vertebrate hosts by blood-taking vectors, mainly Aedes and Culex sp., and are associated with neurological, viscerotropic, and hemorrhagic reemerging diseases, posing as significant health and socioeconomic concern, as they become more and more adaptive to new environments, to arthropods vectors and human hosts. One of the main families that include mosquito-borne viruses is Flaviviridae, and here, we review the case of the Flavivirus genus, which comprises the viruses cited above, using a variety of research approaches published in literature, including genomics, transcriptomics, proteomics, metabolomics, etc., to better understand their structures as well as virus-host interactions, which are essential for development of future antiviral therapies.